The Influence of Digital Marketing Strategy, Price and Customer Experience on Consumer Purchasing Decisions at the Arrahman Perfume Store in Binjai - Tania Putri Maharani; Dewi Nurmasari Pane; Husni Muharram Ritonga (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
As the digital age has changed how consumers interact with products and services, the perfume industry is one of the most affected sectors. As a result, the number of perfumes being produced is increasing, and new perfumes are emerging with various societal trends, which causes competition to become increasingly intense. The purpose of this study is to understand the impact of digital marketing strategies, pricing, and customer experience on consumer purchasing behavior at the Arrahman Perfume store in Binjai. Data collection via a questionnaire given to 80 respondents. The model used with Multiple Regression and processed through SPSS. The results of this study indicate that digital marketing strategies are positively and significantly impacted, as are prices in a positive and significant way and customer experiences in a positive and significant way with regard to consumer purchasing decisions. The Adjusted R Square value is 0.890 or 89%, which means that digital marketing strategy, price and customer experience contribute 89% and the remaining 11% can be explained by other variables that were not studied